The Influence of Social Support and Characteristics of the Stigmatisers on Stigmatising Attitudes Towards People With Mental Illness - Michélle Möhring; Natascha Katharina Krick; Anika Ditze (University of Zurich, IKMZ - Department of Communication and Media Research, 2021)
The stigmatisation of people with mental illness has severe negative consequences for affected individuals. As research in the context of exemplification theory (Zillmann & Brosius, 2000) shows, single-case descriptions of affected individuals (i.e., exemplars) have the potential to either strengthen or reduce stigmatising attitudes towards people with mental illness, in general. We examine the role of depicting social support for exemplars with mental illness (i.e., depression), exemplars' age and sex as well as characteristics of the potential stigmatisers (e.g., sex, relationship status) in generalised stigma-related attitudes towards people with mental illness. A 2 × 2 × 2 online survey experiment with 854 participants was conducted. Univariate ANOVAs yielded main effects and complex interaction patterns of participants' sex and relationship status, as well as combinations of exemplar characteristics. Overall, our results confirm the influence that single-case descriptions can have upon generalised stigma-related attitudes towards people with mental illness. They underline the potential of depicting social support for exemplars with mental illness as well as the consideration of potential stigmatisers' sex and relationship status for (de-)stigmatisation and give starting points for future research in the field of health and anti-stigma-communication.